Strategies for learning glossopharyngeal breathing in boys with Duchenne muscular dystrophy: A feasibility case series - Koshiro Haruyama; Yosuke Yamaha; Miyuki Ito; Tomoyoshi Otsuka; Michiyuki Kawakami (Medical Journals Sweden, 2020)
Objective: To propose alternative learning strategies for glossopharyngeal breathing in patients with Duchenne muscular dystrophy (DMD) and healthy men. Design: A feasibility study with small case series. Subjects: Five boys with DMD and 7 male physical therapists as healthy controls who had not learned glossopharyngeal breathing. Methods: Participants were instructed in a glossopharyngeal breathing protocol, including induction methods comprising sucking motions and phonation with inhalation. The protocol consisted of 1-6 sessions (10-15 min each; total 60 min). Criteria for glossopharyngeal breathing mastery were vital capacity with glossopharyngeal insufflation (VCGI)/VC ratio > 1.10 for the DMD group and > 1.05 for the Healthy group. Feasibility outcomes were time required for mastering glossopharyngeal breathing, self-reported outcomes, adverse events and drop-outs. Results: All participants learned glossopharyngeal breathing within the allocated 60 min. Mean VCGI/VC ratio was 1.31 for the DMD group and 1.09 for the Healthy group. No adverse events or drop-outs were encountered during the protocol. In most cases, self-reported outcomes showed that motivation increased and difficulty decreased. Conclusion: Induction methods for sucking motions and phonation with inhalation for glossopharyngeal breathing learning are feasible. This paper proposes alternative strategies for glossopharyngeal breathing learning in boys with DMD and their instructors.